Cryphonectria naterciae: a new species in the Cryphonectria-Endothia complex and diagnostic molecular markers based on microsatellite-primed PCR. - Bragança, Helena; Rigling, Daniel; Diogo, Eugénio; Capelo, Jorge; Phillips, Alan; Tenreiro, Rogério (Fungal biology, 2011)
In a recent study intended to assess the distribution of Cryphonectria parasitica in Portugal, 22 morphologically atypical orange isolates were collected in the Midwestern regions. Eleven isolates were recovered from Castanea sativa, in areas severely affected by chestnut blight and eleven isolates from Quercus suber in areas with cork oak decline. These isolates were compared with known C. parasitica and Cryphonectria radicalis isolates using an integrated approach comprising morphological and molecular methods. Morphologically the atypical isolates were more similar to C. radicalis than to C. parasitica. Phylogenetic analyses based on internal transcribed spacer (ITS) and β-tubulin sequence data grouped the isolates in a well-supported clade separate from C. radicalis. Combining morphological, cultural, and molecular data Cryphonectria naterciae is newly described in the Cryphonectria-Endothia complex. Microsatellite-primed PCR fingerprinting with (GACA)(4) primer discriminated between C. naterciae, C. radicalis, and C. parasitica.
The following values have no corresponding Zotero field: accession-num: 21872182
Keywords: Ascomycota; Ascomycota: classification; Ascomycota: genetics; Ascomycota: isolation & purification; Chestnut tree; Cork oak tree; Cryphonectria parasitica; Cryphonectria radicalis (GACA)4; DNA; DNA Primers; DNA Primers: genetics; Endothiella gyrosa; Fagaceae; Fagaceae: microbiology; Fungal; Fungal Proteins; Fungal Proteins: genetics; Fungal: genetics; Microsatellite Repeats; Molecular Sequence Data; MSP-PCR; Mycological Typing Techniques; Mycological Typing Techniques: methods; phylogeny; Plant Diseases; Plant Diseases: microbiology; Polymerase Chain Reaction; Polymerase Chain Reaction: methods; Quercus; Quercus: microbiology; RFLP-PCR; Tubulin; Tubulin: genetics

Identification of Portuguese Armillaria Isolates by Classic Mating-Tests and RFLP-PCR Analysis of the ITS1 Region of Ribosomal DNA - Bragança, Helena; Tenreiro, Rogério; Santos, Natércia (Silva Lusitana, 2004)
The diagnosis of Armillaria, a genus including distinct species of highly woody plantpathogenic root-infecting fungi with worldwide distribution, is usually based on morphological characteristics and mating-tests, although the PCR-based restriction fragment length polymorphism (RFLP-PCR), specifically in nuclear rDNA spacers, have also been applied. In the present study, mating-tests and restriction analysis of Internal Transcribed Spacer 1 (ITS1) were used to identify 20 isolates of a Portuguese Armillaria collection. Although the majority of the diploid isolates (80%) could be identified in diploid-haploid pairings, the method is laborious, takes too much time (up to 2 months), and presents a high rate of inconclusive results. The ITS1 region showed to be a reliable molecular marker for A. mellea, in particular when HinfI restriction analysis is applied, since two fragments with 245 bp and 125 bp have been obtained for this most aggressive species whereas 290 bp and 70 bp were produced from isolates of the other European species. As simple molecular techniques are involved and the whole procedure can be performed in one day, A. mellea identification by ITS1 analysis is a clearly accessible and more advantageous tool to plant pathology laboratories, mainly those involved on the control and preservation of forest trees
Keywords: Armillaria mellea; Cork oak; rDNA; RFLP-PCR; Woody plants

Identification of Portuguese Armillaria Isolates by Classic Mating-Tests and RFLP-PCR Analysis of the ITS1 Region of Ribosomal DNA - Bragança, Helena; Tenreiro, Rogério; Santos, Natércia (Silva Lusitana, 2004)
The diagnosis of Armillaria, a genus including distinct species of highly woody plantpathogenic root-infecting fungi with worldwide distribution, is usually based on morphological characteristics and mating-tests, although the PCR-based restriction fragment length polymorphism (RFLP-PCR), specifically in nuclear rDNA spacers, have also been applied. In the present study, mating-tests and restriction analysis of Internal Transcribed Spacer 1 (ITS1) were used to identify 20 isolates of a Portuguese Armillaria collection. Although the majority of the diploid isolates (80%) could be identified in diploid-haploid pairings, the method is laborious, takes too much time (up to 2 months), and presents a high rate of inconclusive results. The ITS1 region showed to be a reliable molecular marker for A. mellea, in particular when HinfI restriction analysis is applied, since two fragments with 245 bp and 125 bp have been obtained for this most aggressive species whereas 290 bp and 70 bp were produced from isolates of the other European species. As simple molecular techniques are involved and the whole procedure can be performed in one day, A. mellea identification by ITS1 analysis is a clearly accessible and more advantageous tool to plant pathology laboratories, mainly those involved on the control and preservation of forest trees
The following values have no corresponding Zotero field: publisher: scielopt
Keywords: Armillaria mellea; Cork oak; rDNA; RFLP-PCR; Woody plants